Associations Between Sarcopenia, Heart Failure and Myocardial Infarction in Patients With Systemic Lupus Erythematosus and Rheumatoid Arthritis - Chang, Ching-Mao; Lin, Jr-Rung; Fu, Tieh-Cheng (Frontiers in Medicine, 2022)
Objectives. To evaluate associations between sarcopenia, type of autoimmune disease and risk of heart failure (HF) and myocardial infarction (MI) in patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Methods. In this population-based, cross-sectional study, discharge data from the 2005-2014 US Nationwide Inpatient Sample (NIS) of hospitalized patients with SLE or RA were extracted and analyzed. Univariate and multivariable regression analyses were conducted to determine associations between sarcopenia, type of autoimmune disease and risk of HF/MI. Results. After exclusions, 781,199 hospitalized patients diagnosed with SLE or RA were included. Among the study cohort, 127,812 (16.4%) were hospitalized with HF, and 12,781 (1.6%) were hospitalized with MI. Sarcopenia was found in only 0.1% of HF/MI patients. Logistic regression analyses revealed that sarcopenia was not significantly associated with presence of either HF or MI. Patients with RA had significantly lower odds of HF than SLE patients (aOR= 0.77, 95%CI: 0.76, 0.79) or MI (aOR= 0.86, 95%CI: 0.82, 0.91). Conclusion. In the US, among hospitalized adults diagnosed with SLE or RA, patients with RA are significantly less likely to have HF or MI than those with SLE. Whether sarcopenia leads to increased HF or MI remains inconclusive. Further studies are warranted to investigate the pathophysiology underlying discrepancies between RA and SLE regarding risk for MI or HF.